PENYELESAIAN SENGKETA HARTA BERSAMA DALAM PERCERAIAN PADA PENGADILAN AGAMA TANGGAMUS - Sulis Tia Ningsih; Lina Maulidiana; Muhammad Lutfi (VIVA THEMIS, 2022)
Marriage is basically a bond of love between a man and a woman who are expected to live together until the end of their lives, but not all marriages end happily. Some marriages end in divorce based on the couple's inability to reconcile. One of the impacts of divorce is the emergence of joint property disputes. The purpose of writing this thesis is to find out the provisions for resolving joint property disputes in divorce at a religious court and to find out the basis for judges' considerations in deciding disputes on joint property case No. 0308/Pdt.G/2018/PA. Mr.This study uses normative juridical and empirical juridical research methods. The data were obtained through the literature and the results of interviews with Maswari as a judge at the Tanggamus Religious Court and analyzed using qualitative.The results of the research show that the provisions for resolving joint property disputes in divorce are the authority of the Religious Courts based on the provisions of Letter (a) point 10 Explanation of Number 37 of Law Number 3 of 2006 concerning Explanation of changes to Article 49 of Law Number 7 of 1989 concerning Religious Courts and in provisions regarding dispute settlement are prioritized through peace in the mediation stage, if there is no peace agreement then it will proceed to the main case according to procedures in the Civil Procedure Code and the basis for consideration of judges in deciding disputes on joint property case No. 0308/PDT.G/2018/PA. Tgm., dividing joint assets in the form of assets in the form of land and buildings, rental proceeds of joint property assets, business assets and assets in the form of debts of each party, both the Plaintiff and the Defendant, receive a half share based on the provisions of Article 97 of the Compilation of Islamic Law.